Feasibility of Nuclear fusion of _1^1H+_3^7Li in TCT reactor - B.M. Dyavappa (East European Journal of Physics)
The feasibility of nuclear fusion reaction 11H+37Li →224He (17.5 MeV), for generation of electric power in nuclear reactors is presented. The fusion cross-section of nuclear reaction for the projectile beam of whose energy ranges from 1 keV to 1×104 keV in the centre-of-mass frame is computed with the aid of GEMINI++ statistical decay model. The Maxwellian average of the product of the fusion cross-section and the relative velocity of projectile and target <συ> gives the fusion reaction rate. The fusion reaction rate should be sufficiently high to produce more nuclear fusion electric power. The energy multiplication factor (ζ) of nuclear fusion is defined as the ratio of nuclear fusion energy EF generated to injected energy of projectile beam (EP), i.e., ζ=EF/EP. The lower energy loss rate and higher fusion reaction rate should contribute higher value of the energy multiplication factor (ζ). The Energy multiplication factor (ζ) for nuclear fusion of 11H+37Li, variation with projectile beam energy is presented. The energy multiplication factor can be enhanced by clamping (or fixing) of projectile beam energy at a suitable value. The clamping of the projectile beam energy defers slowing down process of projectile beam and compensates the Coulomb drag by the bulk plasma, thus the energy multiplication factor increases. The variation of the Energy multiplication factor (ξ) for nuclear fusion of 11H+37Li →224He, with projectile beam energy clamping (or fixing) is also presented.